Uma filosofia do futuro: religião e ateísmo em Ludwig Feuerbach - Lira, Jéssica de Souza (2017)
To think of the religious phenomenon from the proposals of Ludwig Feuerbach consists in the solid development of a critique of Christianity and its interference in western culture. The aim of the present research is to analyze the course of Feuerbach 's philosophy towards the reform of philosophy, which establishes the philosophy of the future, here understood as the philosophy of religion. The critical analysis of religions carried out by the philosopher composes the scenario of a new religion philosophy, which approaches the religious phenomenon as one of the elements present in human life; religion is understood as action in the world and must therefore be faithfully referenced to its expression. Investigate religion in its essence constitutes the task of the new philosophy of religion and this is how Feuerbach analyzes it, seeking to understand it from its essential point of view, that is, from the human perspective. His anthropological atheism emerges as a denial of everything that denies man, including christian and absolutist theology, who chose a world thought only as the real world; the criticism of pagan and christian religions made through his atheism forms the basis of his philosophy of the future. The critique of Hegelian thought also insists, in this sense, as a significant part of the new philosophy of religion in affirming the sensible world as a principle both for philosophizing and for religious activities themselves. The problem of religion approached from its essential point of view to make feasible the realization of a project that gives free expression to man as being in the world, thus achieving his emancipation and producing the new philosophy that recognizes all the dimensions of the human as its own contente. For the composition of the research a bibliographical review was developed and the deductive method was used, so that the presentation of the theories is based on works of the philosopher and some commentators. The conclusive applications point to the new form of philosophy proposed by Feuerbach as a philosophy of religion that inaugurates a human perspective of analyzing religions instead of despising corporeality and materiality, part of them as a presupposition for the emancipation of man through reason free, that part of the only rational being and its sensitivity.